Pengaruh kualitas aparatur daerah, dan sistem informasi terhadap manajemen aset di Kabupaten Oku Selatan - Septriyani, Septriyani (Co-Creation : Jurnal Ilmiah Ekonomi Manajemen Akuntansi dan Bisnis, 2022)
This study aims to determine the effect of the quality of local apparatus, and information systems on Asset Management in the South Oku district government, South Sumatra province. The population in this study are goods users, user goods administrators and assistant user goods managers in each regional device organization. The data used in this study is primary data obtained from distributing questionnaires to respondents. This study uses multiple linear regression analysis model with the help of SPSS software. The results showed that: (1) the quality of the regional apparatus and information systems partially positive and significant effect on asset management and (2) the quality of the regional apparatus and information systems simultaneously had a positive and significant effect on asset management. It can be concluded that the quality of regional apparatus and information systems has an impact on asset management.